ANALYSIS OF TRANSFORMATIONAL LEADERSHIP STYLE AND WORK ETHIC ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE AT THE REGIONAL FINANCE AND ASSET AGENCY OF NORTH SUMATRA PROVINCE - Madaniyah Fitrahayati; Elfitra Desy Surya; Mesra B (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of transformational leadership style and work ethic on employee performance with work motivation as an intervening variable at the Regional Finance and Asset Agency of North Sumatra Province. The research method used is a quantitative approach with data collection techniques through distributing questionnaires to employees. The number of samples was determined by purposive sampling technique with a sample size of 80 respondents. Data analysis was carried out using a path analysis model to see the direct and indirect effects between variables. The results of the study indicate that transformational leadership style and work ethic have a positive and significant effect on employee work motivation. Furthermore, work motivation has a positive and significant effect on employee performance. In addition, transformational leadership style has a positive and significant direct effect on employee performance, but work ethic has a positive but not significant effect on employee performance but its indirect effect through motivation is positive and significant. These findings indicate that work motivation is able to mediate the effect of transformational leadership style and work ethic on employee performance. This study is expected to contribute to management in formulating strategies to improve employee performance through strengthening transformational leadership, instilling work ethic, and increasing work motivation.